Glisten and Glint: The Ajay Way - Horgan, Mervyn (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2025)
Mervyn Horgan reflects on his relationship with Ajay Heble, from the start of his work at the University of Guelph to present day.